Rapid Convergence of Solution for Hybrid System with Causal Operators - Wang, P.; Li, Z.; Wu, Yong Hong (Hindawi Publishing Corporation, 2015)
We investigated the convergence of iterative sequences of approximate solutions to a class of periodic boundary value problem of hybrid system with causal operators and established two sequences of approximate solutions that converge to the solution of the problem with rate of order k≥2.